North-East England, 1569-1625 : governance, culture and identity - Newton, Diana (Regions and regionalism in history., 2006)
"This study of England's north-eastern parts examines counties Durham and Northumberland as well as Newcastle-upon-Tyne, with its central theme the extent to which the county gentry and urban elites possessed a sense of regional identity. It concentrates on these elites' social, political, religious and cultural connections which extended beyond the purely administrative jurisdictions of the county or town. By concentrating on a series of seismic changes in the area - the demise of its great regional magnates, the rapid upsurge of the coal industry and the union of the crowns - it offers a distinctive chronological coverage, from the latter half of the sixteenth century through to the early seventeenth century. Old stereotypes of the north-eastern landed elites as isolated and backward are overturned while their response to state formation reveals their political sophistication. Traditional views of the religious conservatism of the north-eastern parts are reassessed to demonstrate its multi-faceted complexion. And contrasting cultural patterns are analysed, through ballad literature, the cult of St Cuthbert and increasing exposure to metropolitan "civility", to reveal a series of sub-regions within the north-eastern reaches of the kingdom."--JSTOR website (viewed May 26, 2017)